Algorithmic approaches to ostomy management: An integrative review - Corey Heerschap; Britney Butt (Wiley, 2021)
Abstract Objective The aim of this review is to describe approaches to ostomy management utilizing algorithmic approaches found within the literature. Design An integrative review approach was used based on a modified Cooper's five‐stage research review framework. Data Sources Systematic searches occurred using the CINAHL and MEDLINE databases searching for peer‐reviewed, English publications. Review Methods There were 640 articles identified through the review process, 608 of which were excluded based on title and abstract review. The remaining 12 articles were assessed in full text after which two studies were removed as duplicates and six studies were excluded based on inclusion/exclusion criteria. Four studies were included in this synthesis. Studies were critically analysed using a critical appraisal tool developed for both qualitative and quantitative study assessments. Results Utilizing inductive content analysis, included literature was presented within two categories: validation of ostomy algorithms and implementation of ostomy algorithms in practice. Four themes emerged from these categories including the following: algorithm validation, identifying underlying causes, focus on accessories and large‐scale implementation. Conclusion No currently available validated algorithms published in full were found during this literature review. Current literature demonstrates the potential benefit for ostomy management algorithms to standardize and improve ostomy patient care. Impact This study sought to determine the availability and supporting research of ostomy management algorithms which may assist in standardizing and improving ostomy care. This review has demonstrated a lack of available ostomy management algorithms. Given the potential benefit of ostomy algorithms identified within the literature, further studies should be completed to develop, validate and test new ostomy management algorithms.